Лектин Phaseolus vulgaris (PHA) як потенційний модулятор захисних та репаративних процесів в клітині - Карпова, І.С.; Лило, В.В.; Коцаренко, К.В.; Рубан, Т.П.; Мацевич, Л.Л.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2013)
Aims. Optimization of processing conditions of human cells with preparations of PHA and its isoforms to study their modulating effect on the MGMT gene expression. Methods. Object of study: standard (Hep-2 – laryngeal cancer) and obtained in our laboratory (4BL – cells derived from peripheral blood) human cell lines. Cytotoxicity was assessed with MTT assay at a wavelength of 570 nm. For light microscopy the preparations were stained according to Giemsa-Romanovsky. Identification of MGMT protein in cell extracts was performed by using Western blot analysis. For protein loading control there was used the densitometry control of the total amount of protein transfered to the membrane (Scion Image program). Results. According to the results of MTT analysis all lectin preparations at a concentration of 20 mkg/ml exhibited a weak cytotoxic effect. At a concentration of 2 mkg/ml isoforms demonstrated the opposite directed action. Morphological analysis revealed some of action features of every lectin product on the cell population. Western blot analysis showed that all studied lectin preparations affected the level of expression of the MGMT modified form (48 kDa) in the 4BL cell line. The concentration dependence (obtained for PHA-P) was of nonlinear character. At a larger concentration (20 mkg/ml) there was observed the inhibitory effect, which was replaced by a stimulating action of a lower dose (2 mkg/ml). Conclusions. Conditions of human cell treatment in vitro with PHA and its isoform preparations have been optimized. It was found that at the concentration 2 mkg/ml isoforms exhibit opposite directed effects: РНА-L decreases and РНА-E increases the amount of metabolically active cells. Both PHA and its isoforms were shown to modulate the expression of repair enzyme MGMT at the level of the modified (48 kDa) protein form. The data obtained serve as a starting point for further research of pathways and mechanisms of lectin action on DNA repair processes as a components of genome protection system.